2018
DOI: 10.1089/ham.2018.0027
|View full text |Cite
|
Sign up to set email alerts
|

Case Report of Frostbite with Delay in Evacuation: Field Use of Iloprost Might Have Improved the Outcome

Abstract: Irarrázaval, Sebastián, Pablo Besa, Emmanuel Cauchy, Prativa Pandey, and Jorge Vergara. Case report of frostbite with delay in evacuation: field use of iloprost might have improved the outcome. High Alt Med Biol 00:000-000, 2018. -Frostbite is a common injury in high altitude medicine. Intravenous vasodilators have a proven efficacy and, recently, have been proposed as a safe outpatient treatment. Nevertheless, the lack of availability and consequently delayed application of this treatment option can result in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…However, the rewarming method was not consistently described. Eight studies reported rapid rewarming with immersion in hot water [ 41 , 42 , 44–46 , 49 , 52 , 54 ]. Others simply stated that rewarming had occurred.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the rewarming method was not consistently described. Eight studies reported rapid rewarming with immersion in hot water [ 41 , 42 , 44–46 , 49 , 52 , 54 ]. Others simply stated that rewarming had occurred.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperbaric oxygen therapy (HBOT) was used in six studies [ 42 , 43 , 48 , 49 , 54 , 55 ]. Many studies did not describe their HBOT protocol beyond the number of days they used the treatment for.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Perhaps, the most significant case report yielded as part of the search is that of a single case described by Irarrazaval et al [ 26 ]. After a challenging evacuation, a patient was treated with iloprost 75 h after initial symptoms.…”
Section: The Remote Use Of Iloprost In Freezing Cold Injurymentioning
confidence: 99%